Analysis of Factors Affecting Sweet Bread Production - Sofitaria, Avinda; Permai, Ni Made Suyastiri Yani (Journal of Agricultural Social and Business, 2025)
This study aims to (1) analyze the influence of raw materials, supporting materials, and labor on the production of sweet bread at Kedai Djoen Malioboro, (2) analyze the condition of the business scale on the production of sweet bread at Kedai Djoen Malioboro. The type of research used is quantitative descriptive with a case study approach. Data analysis techniques include classical assumption tests, multiple linear regression analysis, and return to scale analysis. The results of the study indicate that the factors that influence the production of sweet bread at Kedai Djoen include raw materials (wheat flour), supporting materials (chicken eggs, powdered milk, granulated sugar, salt, arrowroot flour, and chocolate) and labor. Meanwhile, supporting materials such as butter, roombutter, wet yeast, and bread improver do not affect production. The return to scale value is 0.892 <1, which means that the condition of sweet bread production at Kedai Djoen is on a decreasing return to scale business scale. The proportion of additional production factors for raw materials, supporting materials and labor is greater than the proportion of additional production of sweet bread.